Pengembangan LKPD Cerita Hikayat Bermuatan Toleransi pada Siswa SMA Kelas X - Nila Safina; Mulia Rizki (Keguruan, 2022)
LKPD is a sheet containing tasks that must be done by students and equipped with instructions or steps to complete the tasks ordered in the activity sheet. The research method used is 4D development. The results obtained from the assessment of material experts were the total score in the first stage of validation was 94 with an average of 4.47 that indicated the "very valid" category, in the second stage of validation the score obtained was 78 with an average of 3.71 that indicated the "valid" category. Thus the results obtained from material experts showed the "valid" category, that means the product is feasible and can be used. In the assessment of design experts, the total score obtained in the first stage of validation was 58 with an average of 4.83 indicating the "very valid" category, in the second stage of validation the total score obtained was 57 with an average of 4.75 indicating the "very valid" category. Thus the results obtained from design experts showed the "very valid" category, which means the product is feasible and can be used.